Geometrical Dimensioning and Tolerancing for Design, Manufacturing and Inspection : A Handbook for Geometrical Product Specification Using ISO and ASME Standards - Henzold, G., author 342126; ScienceDirect (Online service) 7722 (Oxford : Butterworth-Heinemann, 2021)
Geometrical Dimensioning and Tolerancing for Design, Manufacturing and Inspection: A Handbook for Geometrical Product Specification Using ISO and ASME Standards, Third Edition presents the state-of-the art in geometrical dimensioning and tolerancing. The book describes the international standardization in this field while also indicating how it differs from the American Standard ASME Y14.5M. The general principles of geometric dimensioning and tolerancing are described, helping users define precision-related specifications unambiguously and consistently with the constraints of the manufacturing and inspection processes. Principles for the inspection of geometrical deviations are given, along with a basis for tolerancing suitable for inspection.